2021
DOI: 10.1037/xlm0000963
|View full text |Cite
|
Sign up to set email alerts
|

Longer resistance of associative versus item memory to interference-based forgetting, even in older adults.

Abstract: Few studies have compared interference-based forgetting between item versus associative memory. The memory-system dependent forgetting hypothesis (Hardt, Nader, & Nadel, 2013) predicts that effects of interference on associative memory should be minimal because its hippocampal representation allows pattern separation even of highly similar information. In contrast, there should be strong interference effects on extra-hippocampally represented item memory. We tested this prediction in behavioral data from 3 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…While earlier work suggests that delay and interference have similar effects on associative memory and item memory across the lifespan with respects to shorter term memory (e.g., lags up to 10 seconds) (Chen & Naveh-Benjamin, 2012), results from recent work suggest that item and associative memory may be differentially affected by interval length (Kuhlmann et al, 2021). Specifically, Kuhlmann and colleagues found that while both item and associative memory declined across lags of varying lengths, item memory declined linearly across all lags, while associative memory remained relatively stable at shorter lags (1 and 11 trials), declining only in later lags (24 and 44 trials).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…While earlier work suggests that delay and interference have similar effects on associative memory and item memory across the lifespan with respects to shorter term memory (e.g., lags up to 10 seconds) (Chen & Naveh-Benjamin, 2012), results from recent work suggest that item and associative memory may be differentially affected by interval length (Kuhlmann et al, 2021). Specifically, Kuhlmann and colleagues found that while both item and associative memory declined across lags of varying lengths, item memory declined linearly across all lags, while associative memory remained relatively stable at shorter lags (1 and 11 trials), declining only in later lags (24 and 44 trials).…”
Section: Introductionmentioning
confidence: 93%
“…A power analysis, based upon the sample size of Kuhlmann et al (2021), showed that in order to reach a medium effect size of f = .25, 55 participants in each age group would be needed.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations